2018
DOI: 10.1111/jebm.12311
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spinal needle type on postdural puncture headache among women undergoing Cesarean section surgery under spinal anesthesia: A meta‐analysis

Abstract: Using pencil-point SN appears to be beneficial for preventing PDPH in patients undergoing Cesarean section without increasing any potential adverse effects. Further research addressing the specific gauge of pencil-point SNs, which might further reduce the incidence of PDPH is highly desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
1
19
0
2
Order By: Relevance
“… 11 According to a meta-analysis study, pencil-point needle is helpful to reduce the risk of PDPH (risk ratio (RR) = 0.33, 95% CI = 0.25–0.45). 20 A study done to compare 25- and 27-gauge needle showed that 14.5% of 25-gauge needle experienced PDPH compared with 3.2% of 27-gauge needle with statistically significant difference (p = 0.027). 3 , 23 Another study comparing 22-, 25-, and 26-gauge spinal needles on the incidence of PDPH revealed that 33%, 4%, and 5% of the participants develop PDPH, respectively, with the overall incidence of 8.3% (p = 0.003).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 11 According to a meta-analysis study, pencil-point needle is helpful to reduce the risk of PDPH (risk ratio (RR) = 0.33, 95% CI = 0.25–0.45). 20 A study done to compare 25- and 27-gauge needle showed that 14.5% of 25-gauge needle experienced PDPH compared with 3.2% of 27-gauge needle with statistically significant difference (p = 0.027). 3 , 23 Another study comparing 22-, 25-, and 26-gauge spinal needles on the incidence of PDPH revealed that 33%, 4%, and 5% of the participants develop PDPH, respectively, with the overall incidence of 8.3% (p = 0.003).…”
Section: Discussionmentioning
confidence: 98%
“…The incidence of PDPH may vary with different needle size and types. 6 , 20 22 The use of a large caliber or cutting needle may associate with high incidence of PDPH. 15 The incidence of headache after spinal anesthesia varies greatly among the previous studies with different factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have reported that the rates of PDPH were 5.6% and 17.2% 23,24 . The difference was mainly due to the use of different types and sizes of puncture needles 25,26 . In our study, we used the pencil-point spinal needles and the rate of PDPH was 8%.…”
Section: Discussionmentioning
confidence: 99%
“…General anesthesia is superior to spinal anesthesia in terms of providing more rapid induction, better cardiovascular stability and respiration control, and the low likelihood of hypotensive attacks. However, aspiration of gastric contents and intubation diffi culties are more common when using general anesthesia in pregnant women and comprise the main disadvantages of this method for cesarean sections [8,9]. Apgar score and cord blood gas analysis are parameters used to assess the well-being of the newborn [10].…”
Section: Introductionmentioning
confidence: 99%